Migraine and Medical Ramifications: A Comprehensive Overview Based on Observational Study Meta-Analyses - Chen, Weiwei; Qian, Wenqi; Zhong, Lixian; Jing, Gongwei (Frontiers in Neurology, 2021)
Purpose: An umbrella review was conducted for comprehensively evaluating previous review-based literature together with meta-analysis of observational investigations probing correlations between migraine and medical end-point ramifications in patients. The breadth and validity of these associations were assessed. Methods: Multiple online scientific repositories (including PubMed, Medline, Embase and Web of Science) were investigated (inception-August 2021) for related meta-analyses focusing on links between migraine and all possible health/medical ramification end-points. A summary effect size and 95% CIs were determined for each identified study with such links. Heterogeneity and small-study influence traces were also evaluated. The AMSTAR 2 platform was employed for evaluating standards of methodology, together with objective criteria, for assessing the standards of datasets from each medical end-point scrutinized in this study. Results: A total of 25 scientific reports comprising 10,237,230 participants for 49 meta-analyses of observational studies were selected. Among such 49 outcomes, 30 demonstrated statistical significance (P< 0.05). Significant associations were observed in multiple diseases, including cardiovascular/cerebrovascular, cerebral, pregnancy-related and metabolic disorders, other outcomes, and mortality. Conclusion: The results showed that migraine increased the risk of 29 health outcomes, though lowered the risk of breast cancer. However, evidence quality was graded as high only for angina. The evidence quality of ischaemic stroke, stroke, MACCE, WMAs, and asthma was graded as moderate. All remaining 24 outcomes had an evidence grade of ‘weak’.